To calculate: The solution of the equation 2(\frac{x}{3}+1)^{2}+5(\

Cordazzoyn 2021-11-20 Answered
To calculate: The solution of the equation \(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}.\)

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

George Burge
Answered 2021-11-21 Author has 6424 answers
Calculation:
Consider the equation, \(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}.\)
Now, simplify the equation \(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}.\)
\(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}.\)
\(\displaystyle{2}{\left\lbrace{\left({\frac{{{x}}}{{{3}}}}\right)}^{{{2}}}+{\left({1}\right)}^{{{2}}}+{2}{\left({\frac{{{x}}}{{{3}}}}\right)}{\left({1}\right)}\right\rbrace}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}.\)
\(\displaystyle{2}{\left\lbrace{\left({\frac{{{x}^{{{2}}}}}{{{9}}}}\right)}+{1}+{\frac{{{2}{x}}}{{{3}}}}\right\rbrace}+{\frac{{{5}{x}}}{{{3}}}}+{5}-{12}={0}.\)
\(\displaystyle{\frac{{{2}{x}^{{{2}}}}}{{{9}}}}+{\frac{{{9}{x}}}{{{3}}}}-{5}={0}\)
Now, taking the least common multiple of the denominator,
\(\displaystyle{\frac{{{2}{x}^{{{2}}}}}{{{9}}}}+{\frac{{{9}{x}}}{{{3}}}}-{5}={0}\)
\(\displaystyle{\frac{{{2}{x}^{{{2}}}+{27}{x}-{45}}}{{{9}}}}={0}\)
\(\displaystyle{2}{x}^{{{2}}}+{27}{x}-{45}={0}\)
This is a quadratic equation so compare the equation from the standard form of quadratic equation \(\displaystyle{a}{x}^{{{2}}}+{b}{x}-{c}={0}\) and identify the values of a, b and c.
Here, a=2, b=27 and c=-45
Now, apply the quadratic formula,
\(\displaystyle{x}={\frac{{-{\left({27}\right)}\pm\sqrt{{{\left({27}\right)}^{{{2}}}-{4}{\left({2}\right)}{\left(-{45}\right)}}}}}{{{2}{\left({2}\right)}}}}\)
\(\displaystyle={\frac{{-{27}\pm\sqrt{{{729}+{360}}}}}{{{4}}}}\)
\(\displaystyle={\frac{{-{27}\pm\sqrt{{{1089}}}}}{{{4}}}}\)
\(\displaystyle={\frac{{-{27}\pm{33}}}{{{4}}}}\)
Firstly, consider the positive sign,
\(\displaystyle{x}={\frac{{-{27}+{33}}}{{{4}}}}\)
\(\displaystyle={\frac{{{6}}}{{{4}}}}\)
\(\displaystyle={\frac{{{3}}}{{{2}}}}\) Now, consider the negative sign,
\(\displaystyle{x}={\frac{{-{27}-{33}}}{{{4}}}}\)
\(\displaystyle={\frac{{-{60}}}{{{4}}}}\)
=-15
Now, to check the solution put the values of x in the original equation,
Substitute x=-15 in the equation \(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}\)
\(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}\)
\(\displaystyle{2}{\left({\frac{{-{15}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{-{15}}}{{{3}}}}+{1}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{2}{\left(-{5}+{1}\right)}^{{{2}}}+{5}{\left(-{5}+{1}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{2}{\left(-{4}\right)}^{{{2}}}+{5}{\left(-{4}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
Further simplified,
\(\displaystyle{2}{\left({16}\right)}-{20}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{32}-{32}{\overset{{?}}{{=}}}{0}\)
0=0
This solution is correct.
Now, substitute \(\displaystyle{x}={\frac{{{3}}}{{{2}}}}\) in the equation \(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}\)
\(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}\)
\(\displaystyle{2}{\left({\frac{{{\frac{{{3}}}{{{2}}}}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{\frac{{{3}}}{{{2}}}}}}{{{3}}}}+{1}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{2}{\left({\frac{{{1}}}{{{2}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{1}}}{{{2}}}}+{1}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{2}{\left({\frac{{{3}}}{{{2}}}}\right)}^{{{2}}}+{5}{\left({\frac{{{3}}}{{{2}}}}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
Further simplified,
\(\displaystyle{2}{\left({\frac{{{9}}}{{{4}}}}\right)}+{5}{\left({\frac{{{3}}}{{{2}}}}\right)}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{\frac{{{9}}}{{{2}}}}+{\frac{{{15}}}{{{2}}}}-{12}{\overset{{?}}{{=}}}{0}\)
\(\displaystyle{\frac{{{24}-{24}}}{{{2}}}}{\overset{{?}}{{=}}}{0}\)
0=0
This solution is correct.
Therefore, the solution set of the equation \(\displaystyle{2}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}^{{{2}}}+{5}{\left({\frac{{{x}}}{{{3}}}}+{1}\right)}-{12}={0}\)
is \(\displaystyle{\left\lbrace-{15},\ {\frac{{{3}}}{{{2}}}}\right\rbrace}.\)
Not exactly what you’re looking for?
Ask My Question
0
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more
...